Technology-Based Learning Management Strategies to Improve Students' Digital Intelligence - Muhammad Shohibuddin; Hamdani; Qomaruddin; Ali Nurhadi (al-Afkar, Journal For Islamic Studies, 2025)
Technology-based learning is learning that is widely implemented in the current era, but there are several gaps in its implementation, one of which is that technology is misused by students for mere entertainment, and there are also challenges that educational institutions must pay attention to in managing learning. To address obstacles and challenges in implementing technology-based learning, good preparation and management is needed by schools and teachers before implementing the learning process, so that in its implementation teachers have insight, anticipation and solutions if learning obstacles occur. There are six things that schools must prepare in managing technology-based learning, namely: qualified human resources, sufficient finances for learning needs, teachers must prepare effective learning theories and practices, supporting infrastructure, learning methods that are appropriate to students' conditions. Apart from that, technology-based learning management strategies that must also be prepared by teachers are: learning implementation plans, which must be created and displayed through technology, in implementing learning, teachers prepare learning activities by utilizing technology, such as learning media, learning materials and teaching materials, and in Teachers can also use technology to evaluate their learning. So with a well-prepared management strategy, technology-based learning will run effectively and efficiently so that it can increase students' digital intelligence.